2021
DOI: 10.3390/ijerph182413116
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Clinician Implementation of Parent-Child Interaction Therapy (PCIT) in New Zealand and Australia: What Role for Time-Out?

Abstract: Background: Parent-Child Interaction Therapy (PCIT) is an effective parent training approach for a commonly occurring and disabling condition, namely conduct problems in young children. Yet, despite ongoing efforts to train clinicians in PCIT, the intervention is not widely available in New Zealand and Australia. Methods: We undertook a cross-sectional online survey of clinicians in New Zealand and Australia who had completed at least the 40-h initial PCIT training, to understand the barriers they encountered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Where the clinician is already seeing a full caseload of PCIT clients (our preliminary research suggests this is unlikely), they will remain eligible for inclusion as we are interested in whether the provision of additional supports might influence the nature and quality of implementation. For example, the PCIT treatment protocol recommends the use of a time-out room in the Parent-Directed Interaction phase, and clinicians have indicated that this requirement can be problematic, which at times results in this phase being omitted or adapted [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Where the clinician is already seeing a full caseload of PCIT clients (our preliminary research suggests this is unlikely), they will remain eligible for inclusion as we are interested in whether the provision of additional supports might influence the nature and quality of implementation. For example, the PCIT treatment protocol recommends the use of a time-out room in the Parent-Directed Interaction phase, and clinicians have indicated that this requirement can be problematic, which at times results in this phase being omitted or adapted [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Existing research suggests that PCIT is viewed as an effective and acceptable intervention to both PCIT-trained clinicians in Aotearoa/New Zealand [ 14 , 15 ], to Indigenous Māori parents when delivered ‘by Māori, for Māori’ [ 13 ], and to families accessing a public mental health service in Aotearoa/New Zealand [ 16 ]. However, a 2019 survey of PCIT-trained clinicians in Aotearoa/New Zealand found that—even where the clinician was using PCIT in their work—the average number of families seen per week for PCIT, per clinician was 1.03 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations